Serum Tau Species in Progressive Supranuclear Palsy: A Pilot Study - Costanza Maria Cristiani; Luana Scaramuzzino; Elvira Immacolata Parrotta; Giovanni Cuda; Aldo Quattrone; Andrea Quattrone (Diagnostics)
Background/Objectives: Progressive Supranuclear Palsy (PSP) is a tauopathy showing a marked symptoms overlap with Parkinson’s Disease (PD). PSP pathology suggests that tau protein might represent a valuable biomarker to distinguish between the two diseases. Here, we investigated the presence and diagnostic value of six different tau species (total tau, 4R-tau isoform, tau aggregates, p-tau202, p-tau231 and p-tau396) in serum from 13 PSP and 13 PD patients and 12 healthy controls (HCs). Methods: ELISA commercial kits were employed to assess all the tau species except for t-tau, which was assessed by a single molecule array (SIMOA)-based commercial kit. Possible correlations between tau species and biological and clinical features of our cohorts were also evaluated. Results: Among the six tau species tested, only p-tau396 was detectable in serum. Concentration of p-tau396 was significantly higher in both PSP and PD groups compared to HC, but PSP and PD patients showed largely overlapping values. Moreover, serum concentration of p-tau396 strongly correlated with disease severity in PSP and not in PD. Conclusions: Overall, we identified serum p-tau396 as the most expressed phosphorylated tau species in serum and as a potential tool for assessing PSP clinical staging. Moreover, we demonstrated that other p-tau species may be present at too low concentrations in serum to be detected by ELISA, suggesting that future work should focus on other biological matrices.